Peran Electronic Word of Mouth terhadap Keputusan Berkunjung Wisatawan di Kawasan Jatigede - Ida Rohida; Dally Nur Arif; Oman Sukirman (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study examines and analyzes the role of electronic word of mouth (e-WoM) on the decision to visit tourists to tourist destinations. In this digital era, communication to obtain information can be done online through electronic word of mouth. This communication is one of the important factors in influencing tourists' decisions to visit a destination. This study used a quantitative method with a survey approach and involved 100 respondents who had visited the Jatigede area. Data collected through distributing questionnaires online were analyzed using simple linear regression analysis to test the relationship between electronic word of mouth variables and visiting decisions. The analysis results show that electronic word of mouth is significant and its role is quite strong in influencing visiting decisions. Information in the form of reviews, and recommendations through social media platforms has proven to be able to increase tourist trust and attract tourists to visit tourist destinations. In addition, the credibility of the source, the number of positive reviews, and the completeness of the information can influence tourists' decisions to visit. The dimensions of electronic word of mouth play a role, namely the dimension of concern for other consumers, the dimension of helping companies, the intensity dimension, the content dimension, and the opinion valance dimension. Thus, stakeholders in the tourism industry need to pay attention to marketing strategies through online review management to increase the number of tourist visits to destinations.